Strategies To Build Youth Interest in Micro, Small and Medium Enterprises in Villages - Hasyim, Rois; Widyaningsih, Bekti (INCOME: Innovation of Economics and Management, 2024)
Micro, Small and Medium Enterprises are businesses that play an important role in the national economy. At this time, MSMEs are intensively running in various regions in Indonesia. There are many MSME resources that have not been established The formulation of this research problem is How the strategy of youth interest in MSME businesses in this study has the purpose of finding out strategies to attract the interest of local youth in developing their businesses. It is hoped that this research will have theoretical and practical benefits that will help in implementing strategies in developing businesses. In this study, a type of qualitative research is used, where the technique of determining the place uses the method of reviewing journal articles that discuss the strategy of youth interest in MSME businesses, MSMEs are a business that plays an important role in the national economy. At this time, MSMEs are intensively running in various regions in Indonesia.